Ongoing challenges and future directions of human papillomavirus vaccination - O. S. Alyautdina; V. Yu. Prilutskaya (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2020)
Cervical cancer caused by human papillomavirus (HPV) types 16 and 18 is one of the most common cancer types in women. Other high-risk HPV types may cause vaginal cancer, vulval cancer, penile cancer, anal cancer, head and neck cancer. Low-risk HPV types, such as 6 and 11, can cause anogenital warts and recurrent respiratory papillomatosis. These diseases may be prevented by vaccinating women and men before contracting the virus. The aim of the study was to summarise current data on using vaccines for the prevention of HPV-associated diseases. Currently, there are three HPV vaccines available on the market: Cervarix®, Gardasil®, and Gardasil®9. Extensive clinical and post-licensing studies show that these vaccines are safe and highly effective (up to 100 %) in preventing vaginal, vulval, and cervical intraepithelial neoplasias when administered to patients who were not previously infected with these HPV types. However, there are a number of unresolved issues that encourage further clinical research to find a universal vaccine. First of all, the effectiveness of these vaccines is limited to the HPV types covered by a particular vaccine. It was only in 2011 that the question was raised about the need to vaccinate males. Also, the recommendations on the frequency of vaccination are periodically revised in line with new immunogenicity study results. Reducing the frequency of immunisation is particularly relevant for developing countries with limited financial resources and a high incidence of cervical cancer. Thus, global vaccination programmes, including those with optimal availability and immunisation frequency for developing countries, higher vaccination coverage in terms of age and sex, and expansion of cancer screening programmes are necessary to eliminate HPV worldwide.